JURIDICAL REVIEW LEGAL PROTECTION ON THE USE OF CUSTOMER DATA BY BRI BANK KC GORONTALO CITY - Savira Nurulhaq, Lidwina; Junus, Nirwan; Towadi, Mellisa (Journal Evidence Of Law, 2023)
The use of customer data is crucial in the banking world, especially in the increasingly advanced digital era. The purpose of this study is to find out how the scheme of using customer data by banks and how to overcome if there is a data leak. The method used is to use sociological juridical research methods, using descriptive qualitative research approaches and interactive analysis techniques. The results of this study are: Problems arise because the issue of data protection problems and customer information in Indonesia has become a new problem in the banking world. On the other hand, adequate forms of protection for a customer's right to privacy have not been implemented into legal instruments. Similarly, the existence of various laws that have the authority to manage a person's data and information is not given a limit to avoid violations that result in unprotected data and information of a person.